The Effects of Some Physico-Chemical Parameters and Seasons on Fish Species Diversity, Caught by Beach-Seine Net in Akköy Lagoon, Aegean Sea - Cemil SAĞLAM (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries, 2021)
The study was carried out monthly between 2014 and 2016 in Akköy Lagoon, Southern Aegean Sea. Experimental beach seine net was used to determine the species diversity in the lagoon. Fishing operations were carried out in triplicate at two different stations. Sea surface temperature (°C), salinity (‰), dissolved oxygen (mg.l-1) and pH were measured. Abundance, species richness (S) and Shannon (H) index values were computed to determine species diversity. A total of 1878 fish specimens from 17 species belonging to 9 families were captured by the beach seine net. The Mugilidae family with five species was represented by the highest catch rates among all the families. According to Canonical Correspondence Analysis (CCA), the diversities of fish species were strongly influenced by environmental parameters. Results indicated that Chelon ramada, Mugil cephalus and Chelon saliens were dominant in the winter and autumn and showed positive correlation with DO. Chelon auratus and Sparus aurata were dominant in the spring and Solea solea, Chelon labrosus, Lithognathus mormyrus, Sardina pilchardus, Boops boops, Zosterisessor ophiocephalus, Mullus spp. and Syngnathus spp. were dominant in the summer and showed positive correlation with SST, pH and salinity. Atherina boyeri, Aphanius fasciatus, Blennius spp. and Pomatoschistus spp. were present in all seasons.